Percepção das características do perfil dos reitores e o desempenho das universidades participantes do Consórcio das Universidades Comunitárias Gaúchas (COMUNG): limites e possibilidades - Palmeiras, Jênifer de Brum (2018)
The theme of this Master's Dissertation is university management in the context of community universities, emphasizing the relation of the characteristics of the profile of the rector with the organizational performance. Community universities are inserted in the higher education market whose reality challenges them to review their practices and organizational structure under the risk of failing to compromise the quality of offered education, academic excellence and organizational sustainability. University management demands new skills from its managers, among them being able to deal with the specificities of being a community and, at the same time, understanding and anticipating changes in scenarios, recognizing the diversification of areas of activity, the proliferation of technologies in teaching methods , the internationalization and globalization movements of higher education. The main objective of the research is to evaluate the relationship between the characteristics of the profile of university managers and the organizational performance in the universities participating in the Consortium of Community Universities Gaúchas (Comung). As specific objectives, it aims to: (a) describe the process of occupying management positions in selected universities and collegial decision-making bodies, analyzing the institutional statutes and regiments; (b) investigate the profile of university managers at the executive level; (c) select and classify the organizational performance indicators of universities; (d) to compare the profile of managers with the organizational performance of universities, examining their ability to interfere with performance indicators. The research was developed at the descriptive level and the method used is the single case study, considering the universe of Brazilian community universities. The selected case was Comung, a network organization that congregates 100% of the community universities of the State of Rio Grande do Sul. The research subjects are the rectors of these universities. The treatment, analysis and interpretation of the data were performed by the content analysis method and the categorial analysis technique. The results evidenced the existence of a relationship between the characteristics of the manager profile and the performance of Comung community universities. The collegiate structure envisaged in the institutional documents requires profile characteristics of a politically inspired and committed manager with the community and, at the same time, recognizes the need to preserve activities in the margin of economic and financial decisions. In community colleges it is desirable for a rector to have characteristics of a more political than business profile, with a prevalence of personality traits of original, independent, inquiring, creative and daring individuals and at the same time interactive and tolerant, emotionally positiv e and oriented towards others. The results indicate that Comung community universities that have managers with these characteristics present highmanagement performance, which can be explained by the fact that they provide the necessary plasticity for the organization to move with agility to the challenges of the Brazilian higher education context.